Development of PjBL-based Canva Teaching Media with STEM approach to Improve Students' Critical Thinking - Palupi, Endang; Karyanto, Puguh; Sugiharto, Bowo (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
Science is a subject that contains activities to understand the universe through observation and using specific procedures to get a conclusion so that it will be more meaningful and can help improve the quality of human resources if implementing learning that allows students to develop knowledge and the ability to apply their knowledge in dealing with problems in everyday life. This study aims to analyze the characteristics of Canva teaching media based on Project-based Learning (PjbL) with the Science Technology Engineering and Mathematics (STEM) approach to increasing students' critical thinking. Based on predetermined characteristics, analyze the validity of Canva teaching media based on Project-based Learning (PjbL) with the Science Technology Engineering and Mathematics (STEM) approach to increasing students' critical thinking, and analyze the effectiveness of Canva teaching media based on Project-based Learning (PjbL) with the Science Technology Engineering and Mathematics (STEM) approach to increasing students' critical thinking. This study is development research with the ADDIE development model.  The ADDIE model has five stages, namely Analysis, Define, Design, Implement, and Evaluate. The data analysis used in this research is the RASCH model, Anacova test, and t-test. The results of the study can be concluded that the characteristics of Canva teaching media contain the syntax of the PjbL learning model, namely determining fundamental questions, planning product design, preparing a product manufacturing schedule, monitoring project progress, assessing results, and evaluating with detailed explanations integrated in conventional biotechnology science subjects. The feasibility of teaching materials is declared valid in terms of material, media, language, and learning with a validity of 0.89 and feasible to use in science learning to improve students' critical thinking skills. The results of the effectiveness test can be declared effective in improving students' critical thinking skills.